Toxic Effects of Chlorpyrifos on 12th Day Desi Chick Embryo (Gallus gallusdomesticus) - Chaudury, S.; Ansari, M. S.; Abbas, M. N.; Kausar, S.; Iqbal, R.; Saleem, R.; Iqbal, J.; Sabir, S. (The Nucleus, 2017)
The toxicity and lethal effects, on the survival and developmental stages of Gallus gallusdomesticus, of widely used insecticides on the ticks and mites (Arachnida) was investigated. Fertilized eggs of Desihen (Gallus gallusdomesticus) at day 0 of incubation were treated with commercially available Chlorpyrifos insecticide at constant temperature 37 ± 0.5 0C.Five different concentrations of this insecticide (0, 0.12, 0.25, 0.50, and 1% per 100 ?l/egg) were used in this experiment. Data on embryos survival and abnormalities were used to observe hazardous effects on developing embryos after pesticide exposure. The embryo mortality, ratio of abnormal embryos were statistically significantly (p < 0.05) different in treated groups compared to untreated. Moreover, toxicity increased with concentration in all experimental groups. The application of Chlorpyrifos (organophosphate) insecticide maybe potentially harmful to embryonic development of birds and other animals.